2000
DOI: 10.1038/sj.cdd.4400663
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair is activated in early stages of p53-induced apoptosis

Abstract: Abstractp53 is a complex molecule involved in apoptosis, cell cycle arrest, and DNA repair. Since apoptosis may play an important role in deletion of neoplastic cells, an understanding of the mechanism of p53-induced apoptosis may be critical for possible future therapeutic interventions. Recent evidence suggests that p53-induced apoptosis may involve members of the nucleotide excision repair (NER) family, linking these two cellular events. Our work using a temperature-sensitive p53 construct further analyzes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 51 publications
4
52
0
Order By: Relevance
“…28 -30 It has been suggested that p53 play a role in regulating NER, especially the GGR subpathway. [31][32][33][34][35][36] As shown in our experiment, a heterozygous loss of p53 appears to act synergistically to a NER defect in tongue tumor induction. The bulky DNA lesions elicited by 4NQO are known to substrate for GGR and 4NQO-DNA damage per se provokes up-regulation of p53.…”
Section: Discussionmentioning
confidence: 82%
“…28 -30 It has been suggested that p53 play a role in regulating NER, especially the GGR subpathway. [31][32][33][34][35][36] As shown in our experiment, a heterozygous loss of p53 appears to act synergistically to a NER defect in tongue tumor induction. The bulky DNA lesions elicited by 4NQO are known to substrate for GGR and 4NQO-DNA damage per se provokes up-regulation of p53.…”
Section: Discussionmentioning
confidence: 82%
“…Initial results from our laboratory have shown that DNA repair is activated early in p53-induced apoptosis, and that early stages may indeed be reversible. 32 This current work follows up on these initial findings and provides more evidence that early stages of p53-induced apoptosis are reversible. Using a temperaturesensitive p53 cell line (p53ts), we show that p53 induces PS-flipping in these cells.…”
Section: Introductionmentioning
confidence: 99%
“…32 To substantiate these results, we have further analyzed p53-induced apoptosis and its reversibility. We have used a temperature-sensitive p53 cell line (p53ts) in which p53 in inactive at 378C.…”
Section: Ps Is Externalized By P53 Activationmentioning
confidence: 99%
“…Early stages of apoptosis may be reversible, as shown by Geske et al, [2000] possibly due to the activation of DNA repair. However, the disruption of the MMP is regarded to be an early, albeit already irreversible stage of apoptosis.…”
Section: Only Early Removal Of Mtbitc Saves the Cells From Apoptosismentioning
confidence: 99%